SLAVERY IN ‘BILAL: A NEW BREED OF HERO’ AND ’12 YEARS A SLAVE’ FILMS - Fitri Hafsyari; Bunyamin Faisal (Universitas Islam Negeri Sunan Gunung Djati, 2021)
This paper discusses slavery in Bilal: A New Breed of Hero film and 12 Years A Slave film. From the title of this paper, it would be known that the objects for this research are Bilal: A New Breed of Hero film and 12 Years A Slave film. The focus of this paper is to seek the portrayal of slavery and its relationship with economic and religion. To analyze both objects, the theory of slavery from Kevin Bales is employed, which sees that slavery is a state marked by the loss of free will. In addition, the theory of Marxism by Karl Marx as a literary theory to assist this research is also used since it is related to examine two antagonistic classes, which in this case, between slave and freeman. They are also used to discuss economic and religion. Besides, the researcher is going to compare both objects by using comparative literature. The method used in this research is descriptive analysis method and comparative literature method. As a result of the analysis, Bilal in the movie is not in accordance with what Karl Marx’s theory that said ‘someone will not contemplate about mental production such as religion, philosophy, and ethics (morality) before he fulfils his economy and basic needs, because maintaining economic power is the motive behind those things’. Bilal does not represent this theory because he is not materialist. Besides, he embraced Islam firmly, so even he was a slave and economically he had nothing, but he chose to prioritize religion (which is included in mental production) before economy (material production). Keywords: slave; slavery; economy; religion; Marxism